MEMBANGUN FONDASI MORAL: PENTINGNYA KEWARGANEGARAAN DI SEKOLAH DASAR: Penelitian Kualitatif - Rahman, Anisa; Wijaya, Aris; Bungana, Reh; Setiawan, Deny (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
This study discusses the importance of citizenship education in elementary schools as an effort to build the moral foundation of students from an early age. The current shift in moral values within society demands comprehensive character education in schools. Through citizenship education, students are taught their rights and duties as citizens, as well as moral values such as responsibility, honesty, and cooperation. This research aims to examine the role of citizenship education in shaping students' moral character from an early age, focusing on the development of students' personal and social competencies to become good citizens. The study employs a qualitative method with a literature review to analyze various relevant sources. The results of the study indicate that the role of teachers is crucial in integrating citizenship values into the curriculum and guiding students through learning and extracurricular activities. With good moral education, students are expected to grow into ethical individuals who actively contribute to national development.